2023
DOI: 10.3390/buildings13061405
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to In Situ Evaluation of Timber Structures Based on Equalization of Non-Destructive and Mechanical Test Parameters

Abstract: This paper addresses the challenges in evaluating the structural performance of built structures using non-destructive methods and in situ tests. Such an examination of structural properties, without their sampling, is a diagnostic improvement, especially for historical heritage buildings, where it is not allowed to violate their physical integrity. Therefore, the research proposes a non-destructive testing method based on the equalization of the mechanically and non-destructively determined parameters of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Researchers have also demonstrated the effectiveness of scanning laser Doppler vibrometry (SLDV) [18] on inspecting inlaid wood and easel paintings [19] based on vibration and ultrasound. Moreover, Josifovski et al [20] reported the feasibility of using ultrasound and X-rays for in situ evaluation of timber structures. On the other hand, guided wavebased approaches provide another avenue whose analytical models, though complex, can describe wave propagation in anisotropic materials [21].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also demonstrated the effectiveness of scanning laser Doppler vibrometry (SLDV) [18] on inspecting inlaid wood and easel paintings [19] based on vibration and ultrasound. Moreover, Josifovski et al [20] reported the feasibility of using ultrasound and X-rays for in situ evaluation of timber structures. On the other hand, guided wavebased approaches provide another avenue whose analytical models, though complex, can describe wave propagation in anisotropic materials [21].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been employed to evaluate timber structures in the field of non-destructive quality control. These techniques include visual inspection, ultrasound testing, infrared thermography, acoustic emission, resistography, moisture-content tests, vibration-based methods, and others [16][17][18][19][20]. Each technique offers unique advantages and limitations, and their effectiveness depends on factors such as the type of defect, accessibility, and the size and configuration of the timber elements.…”
Section: Introductionmentioning
confidence: 99%